Woody tissue photosynthesis increases radial stem growth of young poplar trees under ambient atmospheric CO2 but its contribution ceases under elevated CO2. (29th June 2020) - De Roo, Linus; Lauriks, Fran; Salomón, Roberto Luis; Oleksyn, Jacek; Steppe, Kathy
Abstract: Woody tissue photosynthesis (Pwt ) contributes to the tree carbon (C) budget and generally stimulates radial stem growth under ambient atmospheric CO2 concentration (aCO2 ). Moreover, Pwt has potential to enhance tree survival under changing climates by delaying negative effects of drought stress on tree hydraulic functioning. However, the relevance of Pwt on tree performance under elevated atmospheric CO2 concentration (eCO2 ) remains unexplored. To fill this knowledge gap, 1-year-old Populus tremula L. seedlings were grown in two treatment chambers at aCO2 and eCO2 (400 and 660 ppm, respectively), and woody tissues of half of the seedlings in each treatment chamber were light-excluded to prevent Pwt . Radial stem growth, sap flow, leaf photosynthesis and stomatal and canopy conductance were measured throughout the growing season, and the concentration of non-structural carbohydrates (NSC) in stem tissues was determined at the end of the experiment. Fuelled by eCO2, an increase in stem growth of 18 and 50% was observed in control and light-excluded trees, respectively. Woody tissue photosynthesis increased radial stem growth by 39% under aCO2, while, surprisingly, no impact of Pwt on stem growth was observed under eCO2 . By the end of the growing season, eCO2 and Pwt had little effect on stem growth, leaf photosynthesis acclimated to eCO2, but stomatal conductance did not, and homeostatic stem NSC pools were observed among combined treatments. Our results highlight that eCO2 potentially fulfils plant C requirements, limiting the contribution of Pwt to stem growth as atmospheric [CO2 ] rises, and that radial stem growth in young developing trees was C (source) limited during early phenological stages but transitioned towards sink-driven control at the end of the growing season.